Operational priorities for engaging with India’s private healthcare sector for the control of tuberculosis: a modelling study - Arnab Pal; Nimalan Arinaminpathy; Saskia Ricks; Ananya Singh; Ridhima Sodhi (BMJ Open, 2024)
Objectives To estimate the potential impact of expanding services offered by the Joint Effort for Elimination of Tuberculosis (JEET), the largest private sector engagement initiative for tuberculosis (TB) in India.Design We developed a mathematical model of TB transmission dynamics, coupled with a cost model.Setting Ahmedabad and New Delhi, two cities with contrasting levels of JEET coverage.Participants Estimated patients with TB in Ahmedabad and New Delhi.Interventions We investigated the epidemiological impact of expanding three different public–private support agency (PPSA) services: provider recruitment, uptake of cartridge-based nucleic acid amplification tests and uptake of adherence support mechanisms (specifically government supplied fixed-dose combination drugs), all compared with a continuation of current TB services.Results Our results suggest that in Delhi, increasing the use of adherence support mechanisms among private providers should be prioritised, having the lowest incremental cost-per-case-averted between 2020 and 2035 of US$170 000 (US$110 000–US$310 000). Likewise in Ahmedabad, increasing provider recruitment should be prioritised, having the lowest incremental cost-per-case averted of US$18 000 (US$12 000–US$29 000).Conclusion Results illustrate how intervention priorities may vary in different settings across India, depending on local conditions, and the existing degree of uptake of PPSA services. Modelling can be a useful tool for identifying these priorities for any given setting.